2012
DOI: 10.1002/jbmr.1667
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the E3 ubiquitin casitas B-lineage lymphoma decreases osteosarcoma cell growth and survival and reduces tumorigenesis

Abstract: Targeting receptor tyrosine kinase (RTK) degradation may be an interesting approach to reduce RTK cell signaling in cancer cells. Here we show that increasing E3 ubiquitin ligase casitas B-lineage lymphoma (c-Cbl) expression using lentiviral infection decreased osteosarcoma cell replication and survival and reduced cell migration and invasion in murine and human osteosarcoma cells. Conversely, c-Cbl inhibition using short hairpin RNA (shRNA) increased osteosarcoma cell growth and survival, as well as invasion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 43 publications
2
9
0
1
Order By: Relevance
“…135 Consistently, we recently showed that c-Cbl protein expression is decreased in face of increased EGFR and PDGFR- α expression in human osteosarcoma tumors compared with normal bone. 136 This finding has therapeutic implications as ectopic c-Cbl expression in osteosarcoma cells could reduce the expression of EGFR and PDGFR- α , resulting in decreased cell proliferation and survival, and reduced incidence of lung metastasis in mice. 136 Thus, promoting RTK ubiquitination and degradation by targeting c-Cbl may prove to be efficient at reducing tumor growth and metastasis in cancers in which RTK expression is excessive (Figure 4).…”
Section: Cbl-mediated Ubiquitination: a Potential Target For Therapeumentioning
confidence: 96%
See 1 more Smart Citation
“…135 Consistently, we recently showed that c-Cbl protein expression is decreased in face of increased EGFR and PDGFR- α expression in human osteosarcoma tumors compared with normal bone. 136 This finding has therapeutic implications as ectopic c-Cbl expression in osteosarcoma cells could reduce the expression of EGFR and PDGFR- α , resulting in decreased cell proliferation and survival, and reduced incidence of lung metastasis in mice. 136 Thus, promoting RTK ubiquitination and degradation by targeting c-Cbl may prove to be efficient at reducing tumor growth and metastasis in cancers in which RTK expression is excessive (Figure 4).…”
Section: Cbl-mediated Ubiquitination: a Potential Target For Therapeumentioning
confidence: 96%
“…136 This finding has therapeutic implications as ectopic c-Cbl expression in osteosarcoma cells could reduce the expression of EGFR and PDGFR- α , resulting in decreased cell proliferation and survival, and reduced incidence of lung metastasis in mice. 136 Thus, promoting RTK ubiquitination and degradation by targeting c-Cbl may prove to be efficient at reducing tumor growth and metastasis in cancers in which RTK expression is excessive (Figure 4). This strategy may also be applied to Ewing sarcoma that is associated with increased IGF receptor activity.…”
Section: Cbl-mediated Ubiquitination: a Potential Target For Therapeumentioning
confidence: 96%
“…2F, 2H). However, the effect of c-Cbl silencing on osteoblast markers was not always strictly related to c-Cbl levels, most probably because c-Cbl regulates the degradation of many proteins such as receptor tyrosine kinases [38,44] that may control osteoblast differentiation directly or indirectly.…”
Section: C-cbl Silencing Promotes Osteoblast Proliferation and Differmentioning
confidence: 99%
“…In vivo, la surexpression de c-Cbl dans un modèle murin d'ostéosar-come diminue la formation tumorale ainsi que le développement de métastases pulmonaires dans un modèle murin d'ostéosarcome. Nous avons montré que cet effet antitumoral de c-Cbl in vivo résulte d'une diminution de la prolifération cellulaire et d'une augmentation de l'apoptose des cellules tumorales, effets relayés par une diminution de l'expression des récepteurs PDGFR, EGFR et FGFR2 [33]. Ces données récentes montrent que le rôle antitumoral de c-Cbl passe par l'ubiquitination et la dégradation de ces récepteurs membranaires ( Figure 3B).…”
Section: Rôle Des Protéines Cbl Dans L'ostéogenèseunclassified